Xenophobic rhetoric: Thematic organization of intolerant discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article presents an analysis of xenophobic hate speech in Belarus with the focus on its functioning in online discourse. The study is aimed at determining the thematic structure of xenophobic hate speech as a form of intolerant discourse. Hate speech is understood as a set of language means expressing negative, based on stereotypes or prejudices, attitude towards the addressee as a carrier of values different from those of the addresser, and, as a result, verbalizing one or another type of discrimination or intolerance. The analysis of the topics covered in the online comments made it possible to determine four major thematic categories in the structure of xenophobic hate speech in Belarusian online discourse, each containing two topics: Category 1 “Intuitive assessment”: 1.1. “I do not like them” and 1.2 “Some of them are better/worse than the others”; Category 2 “Characterization of the social group”: 2.1 “Their appearance is different” and 2.2 “Their character and mind is different”; Category 3 “Comparison of the group with other social groups”: 3.1 “They are worse than us” and 3.2 “They are the same as other ‘bad’ social groups” and Category 4 “Position of the group in the discourse community”: 4.1 “They threaten our traditional way of life” and 4.2 “They need to know their place”.
Keywords: xenophobic hate speech; ethnicity-based hate speech; discourse of hate; intolerant discourse; online discourse